Why Do They Not Do More? Analyzing Peacebuilding Actions of Religious Leaders during and after Violent Conflicts - Stipe Odak (Religions, 2024)
This article examines how religious leaders navigate between tensions involving theological ideals of peace and pragmatic realities during violent conflicts. The findings are based on 75 in-depth interviews with Orthodox, Catholic, and Islamic religious leaders in Bosnia-Herzegovina, conducted between the years 2015 and 2017. The paper introduces the concepts of “theological dissonance” to describe mismatches between principles and actions, and “pastoral optimization” for the strategy of maximizing influence under constraints. Factors influencing engagement in peacebuilding include doctrinal traditions, individual differences, organizational capacity of a religious community, effective control over messaging, and audience receptivity. In terms of practical suggestions, the article proposes several measures that could enhance synergy between religious and nonreligious actors working together in this field, most notably, understanding each other’s scopes and limitations and clarifying what “peace” and “peacebuilding” represent to each partner.